Book Review: International Hand-Book on Tourism and Peace - Karki, Neeru (Journal of Tourism and Hospitality Education, 2018)
Not available. About book : Edited by : Cordula Wohlmuther and Werner Wintersteiner Publisher : Centre for Peace Research and Peace Education of Klagenfurt University, Austria Year of : 2014 Publication ISBN No. : 978-3-85435-713-1 Journal of Tourism and Hospitality Education 8 (2018) 97-106